Possibility of reservoir-triggered earthquake occurrence in the Huoi Quang and Ban Chat hydropower dam area - Duan, Bui Van; Duong, Nguyen Anh; An, Tran Thi; Tuan, Vu Minh; Linh, Nguyen Thuy (Vietnam Journal of Marine Science and Technology, 2017)
The possibility of reservoir-triggered earthquake occurrence in the Huoi Quang and Ban Chat hydropower dam area has been assessed based on studying and analyzing the relationships between the reservoir-triggered earthquake occurrence and the following factors: (1) the types of rocks underlying the reservoir; (2) the oscillating reservoir loads on faults in the reservoir area; (3) the incremental stress caused by reservoir loads; (4) the slip tendency of faults in the reservoir area; and (5) the Coulomb stress change of faults in the reservoir area. The results show that these factors have interactive effects and simultaneously contribute to the favorable conditions for reservoir-triggered earthquake occurrence. The Huoi Quang and Ban Chat hydropower reservoirs are located in the area of moderate seismicity; however, with the favorable conditions due to these five factors, reservoir-triggered earthquakes can possibly occur. If reservoir-triggered earthquakes occur, they will be concentrated around the Ban Chat hydropower dam area within a radius of 11 - 12 km and at a depth of about 6 ± 1 km.